DOES MATH-ANXIETY AFFECT SENIOR SCHOOL STUDENTS’ MATHEMATICS PERFORMANCE? EVIDENCE FROM EKITI STATE, NIGERIA - Popoola Abiodun Agnes; Olaniyan Omoniyi Mathew (JME (Journal of Mathematics Education), 2019)
This study identified mathematics anxiety and its effects on students’in performance in Mathematics among Senior School Students in Ekiti State, Nigeria. The sample consisted of 238 SSSII students and 25 math-teachers that were randomly and purposively selected respectively. A questionnaire adapted from the Fennema-Sherman Mathematics Attitudes Scale (FSMAS) was used for the study. Descriptive statistics was used to answer the research questions while t-test was used to test the hypotheses. The study showed that mathematics anxiety exist among senior school students in the study area, which is characterized by feverish feelings in Mathematics class, difficulty in understanding math problem, failure to contribute in Mathematics class, truancy in Mathematics class among others. The study showed that there is a difference in the performance of Mathematics anxious and non-mathematics anxious students as revealed from the t-test. Also, the mean score of the math-anxious student and non math anxious students were found to be 31.84% and 61.31% respectively. It is concluded from the study that Mathematics anxiety affects students’ performance in Mathematics. Concerned stakeholder should implement policies at secondary school level to extend the time of Mathematics class on time table, provide conducive environment and engage innovative teaching methods for the teaching of Mathematics.